JAVANESE TRADITIONAL HOUSE CASE STUDY: VILLAS IN BALI - Rahayu, Ni Nyoman Sri; Putri, I Gusti Ayu Raytina; Negara, I Gede Made Satria Duta (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Rumah Limasan or the Limasan house is one of the traditional Javanese houses that physically has a distinctive character and applies Javanese philosophy. A Limasan house consists of three parts, namely the emper, the central room or living room, and the senthong. It is interesting to explore the representation of Javanese culture in houses and spatial layout in modern buildings that adapt the architecture of Rumah Limasan. Which not only maintains the traditional Javanese culture, but also adds a modern touch that suits today's needs. The application of Javanese house elements such as carvings, natural wood materials, and roof structures. Which has aesthetic value while enriching the residential experience with tangible and intangible Javanese culture. The Limasan house is currently used as a villa, the layout has changed but still has cultural values that can be seen in the ornaments, and the reuse of wood materials.